Budget Saving Potential of Pegfilgrastim Biosimilar for the Treatment of Chemotherapy-Induced Febrile Neutropenia, in Italy - Patrizia Berto; Marco Bellone; Alice Sabinot; Carmine Pinto; Massimo Martino; Daniele Generali; Pier Luigi Carriero; Maria Domenica Sanna (Farmeconomia: Health Economics and Therapeutic Pathways, 2022)
INTRODUCTION: Current Italian guidelines recommend prophylaxis with granulocyte colony-stimulating factors (G-CSFs) to reduce the risk of chemotherapy-induced febrile neutropenia (FN). The availability of G-CSF biosimilars represents an opportunity for savings in the Italian National Healthcare Service (NHS) delivery of care. OBJECTIVE: To assess the cost saving potential associated with the introduction of pegfilgrastim biosimilars to local formularies, compared to the current G-CSF standard practice in Italy. METHODS: A budget impact model was developed to compare the current standard practice of long-acting (LA) and short-acting (SA) G-CSFs use, with a future scenario in which the market share of LA G-CSFs grows due to the more advantageous administration schedule and price of pegfilgrastim biosimilar. The analysis included G-CSF treatment schedules, drug acquisition costs and costs of patient management including hospitalization and ambulatory care. RESULTS: The introduction of pegfilgrastim biosimilar resulted in cumulative 3-year cost savings of € 59,650 and € 41,539 for FN prophylaxis in a potential cohort of 1000 patients with solid tumors and lymphomas, respectively. CONCLUSIONS: The results indicate that the introduction of pegfilgrastim biosimilar is potentially associated with substantial cost savings for the Italian healthcare system.